Evaluation of Intravenous Iron Therapy Response to Manage Anemia in Pregnancy (Journal of Dhaka Medical College, 2018)
Background: Iron deficiency anaemia is a common problem in antenatal patient especially in primigravida in developing world. The study was conducted to evaluate the efficacy of intravenous iron sucrose in antenatal primigravida anaemic cases.Aims and Objectives: The study was conducted to evaluate the response of intravenous iron therapy in anaemic antenatal primigravida patients. The rise of hemoglobin level was predicted after therapy.Materials and Methods: A prospective cross-sectional study was done in the antenatal clinic of Popular Medical College Hospital from January 2016 to December 2016. Primigravida women of e” 18 years with iron deficiency anaemia were included in this study. Pretreatment hemoglobin level was measured. After total dose of calculated iron, intravenous iron sucrose was infused to achieve the target hemoglobin. After completion of therapy hemoglobin was measured 2 weeks and 4 weeks after last dose of iron treatment. Mean, percentage, Chi-square test was done and P value